Dosimetric and biological comparisons of single planning and double plannings for bilateral lung cancer SBRT planning based on the Cyber-Knife system - Guo, Xueling; Su, Huanfan; Wan, Fuying; Zhao, XianZhi; Cao, Tingting; Dai, Zhitao; Zhang, HuoJun (Frontiers in Oncology, 2022)
Abstract: Objective The aim is to investigate the influence of single planning and double plannings on bilateral lung cancer stereotactic body radiation therapy planning from the perspective of dosimetry and biology respectively. Methods Cases with bilateral lung cancer patients who had undergone SBRT with the Cyber-Knife were enrolled, and a single planning and double plannings were designed. The single plan was to optimize the two target volumes in a separate plan, while the dual plan is to optimize two target volumes respectively in two separate plans, then perform dose superposition. Based on the dosimetric results, the biological parameters were calculated. Thus the quality of SBRT plans for those bilateral lung cancer designed by the two methods were compared and evaluated according to the dosimetric and biological results. Results The dose distribution of both planning target volumes and surrounding organs at risk in single planning and double plannings could both meet the clinical prescription requirements. The target conformity index and the new conformity index of PTV were closer to 1 in the double plannings, and the dose gradient GI in the double plannings was smaller than single planning. For organs at risks, the doses received by the double plannings were relatively small. For example, for the normal lung tissue, the V5 and V20 of the double plannings was 4.43%（P>0.05), 10.61%（P=0.017）lower than the single planning respectively. In terms of biological models, for the equivalent uniform dose of normal lung tissue, heart and esophagus, the double plannings was 6.51% (P=0.045), 19.8% (P=0.022), 27.08% (P>0.05) lower than single planning respectively. The results showed that the equivalent uniform dose of normal tissue in the double planning was lower relative to single planning. Conclusions Dosimetric and biological results show that the use of Double plannings have an advantage of protecting normal tissues, and it was suggested that to design double plannings for bilateral lung cancer stereotactic body radiation therapy planning based on Cyber-Knife in the clinical practice.